Taqālid Tuallif Kutub al-Tafsīr al-Malayūwīyah wa al-Jāwīyah wa al-Sundāwīyah: Muḥawalah li Rasm Kharīṭah - Ervan Nurtawab (Studia Islamika, 2005)
This article examines the tradition of translating and interpreting the Qur'an in Javanese, Malay, and Sundanese, with a focus on manuscripts since the beginning of the 20th century. The author of this article has sought to show the dynamics of the translations and interpretations of the Qur'an in these three languages since the 17th century, while further explaining the characteristics of these works in the respective periods.DOI: 10.15408/sdi.v12i3.585